Keanekaragaman Ikhtiofauna di Danau Tapal Kuda (Oxbow Lake) Sungai Bengawan Solo di Kabupaten Lamongan dan Kabupaten Gresik - Taufiq Najib Zamzami; Agung Pamuji Rahayu; Mukti Ali; Septinus Mendrofa (PAKIS JOURNAL INSTITUTE, 2023)
The Bengawan Solo River is one of the major rivers on the island of Java and stretches from Central Java Province to East Java Province. The most dominant type of fish in the Bengawan Solo River flow area is fish from the Cyprinidae family. This research was conducted in Oxbow Lake, Lamongan Regency, and Gresik Regency from May to June 2023. This study aims to determine ichthyofaunal diversity and water quality parameters using quantitative research methods and purposive sampling. Determination of stations based on environmental conditions, consisting of four stations. Based on the research and sampling that have been carried out, a total of 539 fish were obtained from 4 stations in the waters of Lake Horseshoe (Oxbow Lake), consisting of 12 species in 7 families. The diversity index shows the moderate category from 1.99 to 2.71, and dominance shows the low category from 0.08 to 0.26. The average results for physical water quality parameters are temperature 31.8–32.6 °C, brightness 45–59 m, chemical parameters dissolved oxygen (DO) 3.9–4.3, pH 8, nitrite 0.42–0, 54, nitrate 1.5–1.7, and ammonia 0.08–0.15.